Student Participation in Ubudiyah Management: an Educational Model for Strengthening Worship Discipline in the Islamic Boarding School - Jannah, Ikrimatul; Ishari, Nurhafid; Syuhud, Syuhud; Zahroh, Aminatuz (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to describe applying a participatory ubudiyah management model to improve the quality of student worship at the Kyai Syarifuddin Islamic Boarding School, Maqoman Mahmuda Lumajang Dormitory. The research approach used is qualitative, with data collection techniques through participatory observation for 2 months. Interviews are conducted with students, Islamic boarding school administrators, and ustadzah. Document data is a data collection technique. Data analysis is done qualitatively through data reduction, presentation, and verification stages. The results of the study show that the application of the participatory ubudiyah management model in this Islamic boarding school can be seen through three real practical steps, namely joint planning through a deliberation forum between students and ustadzah, habituation of worship with a consistent and structured schedule, and collaborative supervision between ustadzah and students. These three steps not only make students an object of education, but also an active subject who plays a role in maintaining the sustainability and quality of ubudiyah, ultimately strengthening the discipline of their worship. Thus, the participatory ubudiyah education model is relevant to improving the quality of student worship and contributes to enhancing religious character education in Islamic boarding schools as an integral part of Islamic religious education.